Empowering E-Learning: moneywise personal cash flow simulation module / Suhaily Maizan Abdul Manaf ... [et al.] - Abdul Manaf, Suhaily Maizan; Mohamed, Zaimi; Ismail, Fathiyah; Hamzah, Siti Fatimah Mardiah; Abdullah, Sholehah; Mohamad Azmin, Nur Azwani; Affandi, Salwani; Azlan, Nik Noor Afizah (2022)
MoneyWise Personal Cash-Flow Simulation Module has been developed to facilitate students in understanding the elements of personal financial management. The simulation enables the students to experience the essentials of budgeting, record-keeping, and other related activities in money management. The module also provides useful tools and tips for the students to plan and manage their cash flows and financial requirements. In the simulation, the students have assumed the role of individuals with a monthly salary for their chosen career and family scenarios. Based on certain assumptions and events, the students have been required to prepare their family budgets and record daily cash flows for a specified given period. During the simulation, the students have been able to analyse the status of their financial position in various reports, such as the budget template and cash-flow statement. In the meantime, MoneyWise has also featured other tools, such as one-million planner and references on money management. The newly upgraded version is available with additional financial ratios report, namely liquidity ratio, debt-to-asset ratio, solvency ratio, current ratio, and debt-service ratio. These ratio reports enable users to understand and aware of their current financial standing, which are useful for helping consumers to plan their financial matters based on their financial-level information more effectively. Besides, the module is expected to enhance students' potentials to obtain excellent grades in personal financial planning course as well as elevating their skills and readiness to face real-life situations in the future. The system not only functions as an e-learning material and tool but is also useful for individuals to record and manage their daily transactions. MoneyWise is a great e-learning innovation and relevant financial tool in an effort to elevate the level of financial literacy of society, which is in line with the National Strategy for Financial Literacy 2019-2023.